2022
DOI: 10.3390/en15165926
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Heat and Mass Transfer for Williamson Nanofluid over Stretching/Shrinking Sheet along with Brownian and Thermophoresis Effects

Abstract: The purpose of the current study is to investigate the non-Newtonian unsteady Williamson fluid on a stretching/shrinking surface along with thermophoresis and Brownian effects. Basically, the model consists of a time-dependent magnetic field. The fluid is considered to be electrically conducting due to the effect of the external magnetic field. The values of magnetic Reynolds number are so small that the induced magnetic field is assumed to be negligible. In the concentration equation, the effects of Brownian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…NTU represents the number of heat transfer units in the dehumidification channel of LDD (𝑁𝑇𝑈 • ⋅ , . In the process of heat mass transfer between solution and air, the Lewis number 𝐿𝑒 ⋅ in LDD and RIEC is taken as 1 [23], the number of mass transfer units in the primary channel of LDD can be expressed as 𝑁𝑇𝑈 • .…”
Section: Numerical Model Of the Ldd And Riecmentioning
confidence: 99%
See 1 more Smart Citation
“…NTU represents the number of heat transfer units in the dehumidification channel of LDD (𝑁𝑇𝑈 • ⋅ , . In the process of heat mass transfer between solution and air, the Lewis number 𝐿𝑒 ⋅ in LDD and RIEC is taken as 1 [23], the number of mass transfer units in the primary channel of LDD can be expressed as 𝑁𝑇𝑈 • .…”
Section: Numerical Model Of the Ldd And Riecmentioning
confidence: 99%
“…NTU represents the number of heat transfer units in the dehumidification channel of LDD (NTU = α LD1 •A wall m LD1 •c p,a1 ). In the process of heat mass transfer between solution and air, the Lewis number (Le = α LD1 α mLD1 •c pa1 ) in LDD and RIEC is taken as 1 [23], the number of mass transfer units in the primary channel of LDD can be expressed as NTU m = α ms •A wall m a1 . Equations ( 1) and ( 2) can express the latent and sensible heat processes in the microelements in the dehumidification channel.…”
Section: Numerical Model Of the Ldd And Riecmentioning
confidence: 99%
“…Mishra et al [34] conducted finite difference calculations of temperature dynamics in a cross-flow HX under temperature and flow maldistributions for several conditions. Zhu et al [35] performed a numerical investigation on fluid parameters and their impact on heat transfer, and the study concluded that a reduced fluid velocity improves the thickness of the thermal boundary layer. Ishaq et al [36] studied the effect of flow distribution on the performance of a double pipe heat exchanger when adding fins of a diamond shape.…”
Section: Introductionmentioning
confidence: 99%